14P Anti-PDL1/IL-15 fusion protein increases rare effector cells in cynomolgus monkeys and mice. (15th December 2019) - Martomo, S; Lu, D; Polonskaya, Z; Luna, X; Miyara, F; Patel, J
Abstract: Background: Kadmon has generated an anti-PDL1/IL-15 fusion protein (KD033) by combining a proprietary, fully human, high affinity anti-human/mouse PD-L1 antibody with human IL-15. Initial assessment of KD033 showed enhanced tolerability relative to a non-targeted IL-15 fusion protein, in addition to its potent anti-tumor activity and immune memory generation. KD033 increased CD8 + T and NK cells in peripheral blood of humans, cynomolgus monkeys and mice as expected from on target engagement of IL-15. In this study, we evaluated additional immune cell population changes in mice and cynomolgus monkeys treated with KD033. Methods: Tumor size, measured at day 7 in syngeneic subcutaneous CT26 colorectal cancer mouse model after a single KD033 surrogate treatment, was used to define mice as either KD033 responders (decreasing tumor volumes) or non-responders (no change or increasing tumor volumes). Peripheral blood from KD033 responders and non-responders as well as from cynomolgus monkeys treated with KD033 at predose, 24 and 168 hours after dosing was analyzed by flow cytometry for various immune cell populations. Results: Granzyme B + CD8 + T and gamma delta T cells in peripheral blood were specifically increased in KD033 surrogate responder mice. These increases were not observed in non-responder mice. Greater increases in NKT-like cells were also observed in KD033 surrogate best responders. This is in contrast to other immune populations, such as CD8 + T and B cells, which were similarly impacted, in both KD033 surrogate responder and non-responder mice. In cynomolgus monkeys, CD3 + CD4-CD8- cells, which includes gamma delta T cells, were one of the immune populations with the highest increases at 168 hours post dose. Conclusion: KD033 administration increases CD8 + T and NK cells, consistent with IL-15 pharmacodynamics. In addition, analysis of peripheral blood from KD033 surrogate best and non-responder mice demonstrated increases in different immune populations, which can facilitate their use as in-treatment biomarkers of KD033 activity in tumors. Importantly, KD033 administration resulted in increases in rare cytotoxic cells such as NKT and gamma delta T cells in peripheral blood which may contribute to its anti-tumor activity and immunity. Legal entity responsible for the study: Kadmon Corporation LLC. Funding: Kadmon Corporation LLC. Disclosure: S. Martomo: Full / Part-time employment: Kadmon Corporation. D. Lu: Full / Part-time employment: Kadmon Corporation. Z. Polonskaya: Full / Part-time employment: Kadmon Corporation. X. Luna: Full / Part-time employment: Kadmon Corporation. F. Miyara: Full / Part-time employment: Kadmon Corporation. J. Patel: Full / Part-time employment: Kadmon Corporation.